Aeronautical Materials Laboratory staff - United States. Navy; Naval Air Engineering Center (U.S.) (1961)
Group photograph of Aeronautical Materials Laboratory staff members (from left) J. Hartley Bowen, Jr. (Technical Director); Martin J. Devine; and E. Robert Lamson. Assorted machinery, as well as a sign for the laboratory's Chemical Engineering Division, Lubricants Branch, is visible in the background.
Keywords: Aerospace Research Laboratories (U.S.); Employees; Laboratories; Naval Air Engineering Center (U.S.)